Crowdfunding in the Board Games Industry – Game Changer or a Temporary Curiosity? - Nowicki, Michał (Finansowanie społecznościowe w branży gier planszowych – game changer czy tymczasowa ciekawostka?, 2023)
The objective of the article is providing some arguments and proving that, in the case of the board game industry, crowdfunding should be not only seen as an alternative to “traditional” sources of financing, but also should be commonly perceived as a kind of game changer. Bibliometric analyses prove that crowdfunding as a topic is cognitively attractive, and suggest that importance of crowdfunding will grow in the future. The author uses both quantitative and qualitative research methods, techniques and tools. Quantitative research is primarily an in-depth bibliometric and graphical analysis based on WoS CC database resources using VOSViewer and MS Excel software. Qualitative research is a synthetic presentation and analysis of several, intentionally selected, case studies, i.e., hugely successful “crowdfunding campaigns” conducted on kickstarter.com – the most recognizable crowdfunding platform. After reading the content of the article reader should feel encouraged to independently follow issues related to the topic of crowdfunding, as it is “trendy” topic importance of which will grow in the nearest future. Literature analysis shows crowdfunding not only as a source (mechanism) of financing. Crowdfunding is also a phenomenon stimulating, among others, innovation, entrepreneurship, organizational openness, creativity, readiness to co-create. Crowdfunding is a topic that everyone should be interested in – both business practitioners and representatives of the world of science.
Nowicki, M. (2023). Crowdfunding in the Board Games Industry – Game Changer or a Temporary Curiosity? In M. Hajdas (Ed.), Game Changers in Management (pp. 80-97). Publishing House of Wroclaw University of Economics and Business.
Keywords: crowdfunding; gamechanger; kickstarter; board games industry; game changers; branża gier planszowych